Employee commitment to the organization: a comparative quantitative exploration of employees based on role and primary work location at multi-campus community colleges - McKeever, Matthew Timothy, author; Gloeckner, Gene W., advisor; Anderson, Sharon K., committee member; Greene, David, committee member; Lynham, Susan A., committee member (Colorado State University. Libraries, 2018)
This comparative quantitative study explored differences in and predictors of adjunct instructors, administrators, and faculty's affective, continuance, and normative commitment to multi-campus community colleges. Extraneous independent factors included time worked at the college, highest level of education, and age. Attribute independent factors included employee type, and primary work location. Two main constructs that acted as the dependent factors in the research questions were Meyer and Allen's (1991) Three Component Model of Employees Commitment to the Organization and the employees' perception of college leaders' practices of collaboration, communication and empowerment. Research question one explored the relationship between college employment factors (employee type and primary work location) and the employees' commitment to the organization. Factorial ANOVA findings determined there were no significant interaction between the effects of employees' primary work location and employee type on the employees' affective, continuance or normative commitment to the organization. Main effects were found to be significant across adjunct instructors and administrator employee types with administrators' affective commitment to the organization being higher. Research question two explored the relationship between college employment factors (employee type and primary work location) and the employees' perception of college leader's practices of collaboration, communication, and empowerment. Factorial ANOVA findings determined there were no significant interactions or main effects between primary work location and employee type on the employees' perception of college leaders' collaboration, communication or empowerment. Research question three attempted to understand if college employment factors (employee type and primary work location) and employees' perception of college leaders' practices (collaboration, communication and empowerment) were predictors additive to demographic factors (age, time worked at the college, and highest level of education) of employees' commitment to the organization. Multiple linear regression was computed for each of the three components of commitment considering college employment factors and perception of college leaders' practices. (A) Employees' perception of college leaders' practices (β = .69), adjunct instructor employee type (β = -.19), and age (β = .13) contributed significantly to the employees' affective commitment to the organization; (B) The group of factors did not significantly contribute to the employees' continuance commitment to the organization (C) Employees' perception of college leaders' practices (β = .49), and time worked at college (β = .16) contributed significantly to the employees' normative commitment to the organization. Significant findings included differences in the employees' affective commitment to the organization between adjunct instructors and administrator employee types; and the employees' perception of leaders' practices of collaboration, communication, and empowerment were the strongest predictors of employees' affective and normative commitment to the organization.
Keywords: employee commitment; multi-campus college; higher education leadership; community college administration